Light-Based Anti-Biofilm and Antibacterial Strategies - Ambreen Kauser; Emilio Parisini; Giulia Suarato; Rossella Castagna (MDPI AG, 2023)
Biofilm formation and antimicrobial resistance pose significant challenges not only in clinical settings (i.e., implant-associated infections, endocarditis, and urinary tract infections) but also in industrial settings and in the environment, where the spreading of antibiotic-resistant bacteria is on the rise. Indeed, developing effective strategies to prevent biofilm formation and treat infections will be one of the major global challenges in the next few years. As traditional pharmacological treatments are becoming inadequate to curb this problem, a constant commitment to the exploration of novel therapeutic strategies is necessary. Light-triggered therapies have emerged as promising alternatives to traditional approaches due to their non-invasive nature, precise spatial and temporal control, and potential multifunctional properties. Here, we provide a comprehensive overview of the different biofilm formation stages and the molecular mechanism of biofilm disruption, with a major focus on the quorum sensing machinery. Moreover, we highlight the principal guidelines for the development of light-responsive materials and photosensitive compounds. The synergistic effects of combining light-triggered therapies with conventional treatments are also discussed. Through elegant molecular and material design solutions, remarkable results have been achieved in the fight against biofilm formation and antibacterial resistance. However, further research and development in this field are essential to optimize therapeutic strategies and translate them into clinical and industrial applications, ultimately addressing the global challenges posed by biofilm and antimicrobial resistance.